Reduced viability of N. crassa ergosterol mutants on Vogel's medium. - Uwe Hilgert; Hans D. VanEtten (Fungal Genetics Reports, 1995)
Neurospora crassa ergosterol mutants are unable to synthesize ergosterol, the prevalent sterol in most filamentous fungi. These mutants have pleiotropic phenotypes such as reduced mycelial growth, decreased production of conidia, acquired tolerance to the polyene antibiotic nystatin (M. Grindle 1973 Mol. Gen. Genet. 120:283-290) and increased sensitivity to the pea phytoalexin pisatin (K. G. Papavinasasundaram and D. P. Kasbekar 1993 J. Gen. Microbiol. 139:3035-3041). We hoped to use the erg-1 mutant as a means of isolating pisatin detoxifying genes from other fungi by functional complementation for tolerance to pisatin. However, we observed that standard methods used for N. crassa were not suitable for ergosterol mutants because of their low viability on Vogel's minimal medium (H. J. Vogel 1964 American Naturalist 98:435-446).